ECO-BASED REASONED ACTION MODEL: THE ROLE OF MANAGEMENT CONTROL SYSTEM - Eka Ardhani Sisdyani (Universitas Agung Podomoro, 2020)
This paper aims to enrich Fishbein and Azjen’s Theory of Reasoned Action in predicting the emergence of green behavior by adding institutional-based control system to maintain green intention’s stability. Intention’s stability is a crucial construct in realizing green behavior, though, it is affected by several instances such as: resources availability, individual capabilities, new information, and cooperation and commitment of individuals. For that reason, it is plausible to argue that the existence of institutional-based control directing green behavior, such as eco-based management control systems, namely levers of eco-control, can maintain and augment one’s intention to pursue green behavior. Thus, the paper contributes in enriching the knowledge of the emergence and persistence of green behavior in organizations.